Analysis of the Pore Structure of Shale in Ordos Basin by SEM with Nitrogen Gas Adsorption-Desorption - CHEN Sheng-rong; SHUAI Qin; GAO Qiang; TIAN Ya; XU Sheng-rui; HUANG Yun-jie (Yankuang ceshi, 2015)
Identification of porosity in shale is of great significance for exploring mechanism of shale gas. Porosity properties of the shale samples from the Ordos Basin were characterized by multiple techniques including Scanning Electron Microscope(SEM), Mercury Intrusion Porosimetry(MIP), and nitrogen gas adsorption-desorption. Results showed that the shales contained abundant pores that include dissolution pore, microfracture pore, and intergranular pore. The pore sizes range from several to several hundred nanometers. The total surface area ranges from 5.06 to 19.32 m2/g and pore volume has a range of 0.01-0.03 cm3/g. Results indicate that the OrdosBasin Shale develops pores of various types and sizes. The main type of pore is the nano-pore, which is beneficial for the storage of shale gas. Micro-cracks are beneficial for the transportation of shale gas. These results suggest that the basic environment of the Ordos Basin is suitable for the storage of shale gas and that the Ordos Basin may be rich in shale gas.